Design of Quadrilateral Learning with RME Approach for Junior High School Students - Chairunnisa Inayatusufi; Tian Abdul Aziz (JURNAL RISET PEMBELAJARAN MATEMATIKA SEKOLAH, 2021)
The purpose of this study is to provide alternative learning options, with a realistic mathematics education learning design or RME on quadrilaterl material for Junior High School students. This writing uses instructional design to develop a learning model. Learning development is done by analyzing needs and learners. Performance objectives and learning outcomes are discussed in detail and adapted to instructional objectives. The results of this study indicate that a quadrilateral learning design by applying the RME approach is recommended for educators in conducting quadrilateral learning. This happens because learning is based on real life or situations that can be imagined by students which are in accordance with RME characteristics, so that they can help students understand quadrilaterals.